2011
DOI: 10.3389/fpsyg.2011.00128
|View full text |Cite
|
Sign up to set email alerts
|

Increased Alpha-Band Power during the Retention of Shapes and Shape-Location Associations in Visual Short-Term Memory

Abstract: Studies exploring the role of neural oscillations in cognition have revealed sustained increases in alpha-band (~8–14 Hz) power during the delay period of delayed-recognition short-term memory tasks. These increases have been proposed to reflect the inhibition, for example, of cortical areas representing task-irrelevant information, or of potentially interfering representations from previous trials. Another possibility, however, is that elevated delay-period alpha-band power (DPABP) reflects the selection and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 38 publications
(62 reference statements)
5
30
0
Order By: Relevance
“…It is still debated whether alpha oscillation is related to successful maintenance of item information Palva and Palva, 2007;Hsieh et al, 2011;Johnson et al, 2011), or whether it reflects inhibition of task-irrelevant information (Jokisch and Jensen, 2007;Klimesch et al, 2007;Tuladhar et al, 2007;Manza et al, 2014). Our study provided three pieces of evidence to support the maintenance rather than inhibition.…”
Section: Discussionsupporting
confidence: 46%
See 3 more Smart Citations
“…It is still debated whether alpha oscillation is related to successful maintenance of item information Palva and Palva, 2007;Hsieh et al, 2011;Johnson et al, 2011), or whether it reflects inhibition of task-irrelevant information (Jokisch and Jensen, 2007;Klimesch et al, 2007;Tuladhar et al, 2007;Manza et al, 2014). Our study provided three pieces of evidence to support the maintenance rather than inhibition.…”
Section: Discussionsupporting
confidence: 46%
“…However, the precise role of the alpha band in WM is still under debate. Some scholars have proposed that oscillatory alpha activity reflects the inhibition of cortical areas representing task-irrelevant information (Jokisch and Jensen, 2007;Klimesch et al, 2007;Tuladhar et al, 2007;Manza et al, 2014), while others have suggested that alpha oscillation is related to successful maintenance of item information Palva and Palva, 2007;Hsieh et al, 2011;Johnson et al, 2011). Duration maintenance in WM has received much less attention compared with non-temporal stimulus properties, and the relationship between neural oscillation and duration maintenance in WM has yet to be identified.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Hypotheses regarding the alpha rhythm include: (1) an electrophysiological marker of an “idling” state of the brain (Pfurtscheller et al, 1996), (2) suppression of unattended sensory information (Worden et al, 2000; Kelly et al, 2006; Thut et al, 2006), especially in the suppression of task-irrelevant information (Klimesch et al, 2007; Jokisch, Jensen, 2007; Jensen, Mazaheri, 2010), and (3) retention and processing of task-relevant information (Palva, Palva 2007; Johnson et al, 2011). The fascinating and complex roles that alpha range rhythms play in cognitive function have been reviewed (Palva, Palva, 2007; Klimesch, 2012).…”
Section: Discussionmentioning
confidence: 99%